Census of Governments, 1977: Bargaining Units Summary Statistics ([Verlag nicht ermittelbar], 1984)
The Census of Governments is conducted at five-year intervals by the Census Bureau and covers the following major subject areas: governmental organization, taxable property values, government employment, and government finances. The statistics in this data collection were gathered from a subset of units analyzed in the 1977 Census of Governments. Contained in that subset were all state and local governments that had one or more collective bargaining units, and data are provided for each bargaining unit. Information is included on the type of employees represented, whether the unit represented supervisory personnel, and the number of employees represented. Up to l3 bargaining units may be contained in one record, and governmental units with more than 13 units will have more than one record. There are 36 state governments and 12,110 local governments with bargaining units represented in this data collection.